Inhibition of Heme Polymerization Invitro Assay Of Extract of Sirih Leaf (Piper betle Linn.) and Sun Flower Leaves (Helianthus annuus L.) - Ami Tjitraresmi; Moelyono Moektiwardoyo; Yasmiwar Susilawati (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Malaria is a disease that occurs in tropical countries like Indonesia. The incidence of malaria in the world is still quite high and the occurrence of cases of Plasmodium resistance to antimalarial drugs and the widespread of resistance have prompted researchers to look for new antimalarial drugs, especially from natural materials. Betel leaf (Piper betle Linn.) And sunflower leaf (Helianthus annuus L.) have long been used by the people of Indonesia as an antimalarial drug. The purpose of this study was to determine antimalarial activity through inhibition of heme polymerization and determine secondary metabolite compounds by phytochemical screening from betel leaves and sunflower leaves. The heme polymerization inhibition activity assay was carried out by the in-vitro method using a microplate reader at 415 nm and 630 nm wavelengths. IC50 values of betel leaf extract and sunflower leaf were 178.67 μg/ml and 160.10 μg/ml, respectively. Phytochemical screening results from betel leaf showed the presence of flavonoids, polyphenols, tannins, quinones, saponins, and monoterpenoids-sesquiterpenoids, while sunflower leaves contain alkaloids, polyphenols, flavonoids, steroids and monoterpenoids-sesquiterpenoids.Keywords: Piper betle Linn., Helianthus annuus L., Malaria, Heme Polymerization